Executive coaching across cultures: perceptions of black and white South African leaders - Anandlal, Pranesh (My University, 2017)
The objective of this research is to explore the perceptions and experiences of coaching across cultures among white and black leaders in South Africa. The research thus aims to contribute towards an understanding of the role and the impact of cross-cultural executive coaching, both its implications for the coaching intervention and relationship and its application in the wider South African context. Cross-cultural coaching is a contracted coaching engagement between two people from different race groups. Black people refers to people who are citizens of the Republic of South Africa by birth or descent and are African, Coloured or Indian. The research used a qualitative methodology. 16 semi-structured interviews were conducted with executives and managers who had recently experienced cross-cultural executive coaching. The transcripts of the interviews were analysed, resulting in 12 broad themes. The findings revealed that cross-cultural executive coaching pushed personal boundaries on two levels. Not only did female executives push gender boundaries in their selection process, but both male and female executives pushed the boundaries in experiencing different perspective on issues. The executives who had been exposed to diversity early in their lives appear to have successfully embraced cross-cultural coaching. Furthermore, the greater the exposure to international work or life experience early in the executive’s career development, the more welcoming and enhancing the cross-cultural coaching experience was. Most executives acknowledged the importance of exploiting South Africa’s cultural diversity as a business advantage, so the outstanding results in the performance and development of leaders already brought about by executive coaching can be extended further. The findings on what influenced the cross-cultural relationship pointed to the importance of coaches and clients connecting authentically and personally. When coaches listened well and displayed good questioning skills, the relationship flourished. The levels of understanding between coach and executives were critical for the development of the coaching relationship. These findings provide key insights into what makes a good cross-cultural coaching experience. The broader implications for cross-cultural coaching in South Africa include both benefits and challenges to professional, executive development. They show how an absence of cultural awareness and cultural intelligence in cross-cultural coaching can limit benefits, and reveal the opportunities possible in helping heal the wounds of an historically divided nation. The study recommends a fresh look at how we train and prepare cross-cultural coaches for the South African context. As the coaching intervention experience expands, the goal is to adjust and include the development of cross-cultural competency for effective cross-cultural coaching.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management (Business and Executive Coaching) Wits Business School, Johannesburg February 2017
Keywords: Executives--Training of--South Africa; Leadership--South Africa; Diversity in the workplace--South Africa